Postcard from Margaret Ripley to her mother, 5 December 1914 (6238846882) - whatsthatpicture from... (Wikimedia Commons, 2011)
Notice image issue de Wikimedia Commons. Titre: Postcard from Margaret Ripley to her mother, 5 December 1914 (6238846882). Sent by a nurse, Margaret Ripley, to her mother back in England. As far as I can tell (corrections and additions welcome as this one was tricky!) this reads: "We are really going to Paris, Thursday morning 6.30am. There we are to wait til we are wanted. Shall be glad to see [???????] came to see us today nothing definite wait [???????] do not write until I send new address - Asturias [*see comment below] came in again today No parcel. We have much enjoyed these last few days. Went to church Sun We supper in our room. Today and Monday had coffee in bed 9am the others wait on me. Meals in our room & No time to do anything. Had card from Elsie. Hope we shall settle soon but everything seems very vague. Love to all Mar" To the right, above the address, there are some additional notes, I think in another hand. Crossed out, there is a line "Send both back" and then "How about Thursday have asked Mrs Waggs [?] to meet us. Send card to Elsie at once." There is also what I think is the name "Duds" which I have seen on other cards not yet uploaded. For more details of the story behind this album see www.flickr.com/photos/whatsthatpicture/sets/7215762769463...
Droits : Licence CC BY 2.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale; église; transport; Carte postale